2017
DOI: 10.13189/ujg.2017.050303
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Analysis of Water Pan Sites for Pastoralists: A Case Study of Kajiado County in Kenya

Abstract: The paper looks into the analysis of water spatial accessibility by pastoralists in Kajiado County. Since it's a pastoralist area, the demand for water is essential, but due to climate change, the area experiences erratic rains, extreme temperatures and cyclic and prolonged droughts. The need to access improved water supply is considered to boost economic development poverty alleviation. With inadequate water harvesting structures, integrated journal positions the need to excavate more water pans which require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…The study was carried out in Kajiado County which is a large pastoralists area characterized by nomadic life with many in search of pasture due to prolonged dry spells and unpredictable rainfall seasons exacerbated by climate change (Mutua and Boitt, 2017). Due to increased support by the government in the region, the study identified sites that has received immense support on irrigation technologies looking at the impact of smallscale drip irrigation on crop diversification in Kajiado Central in Mashuru, Isinya and Namanga.…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out in Kajiado County which is a large pastoralists area characterized by nomadic life with many in search of pasture due to prolonged dry spells and unpredictable rainfall seasons exacerbated by climate change (Mutua and Boitt, 2017). Due to increased support by the government in the region, the study identified sites that has received immense support on irrigation technologies looking at the impact of smallscale drip irrigation on crop diversification in Kajiado Central in Mashuru, Isinya and Namanga.…”
Section: Methodsmentioning
confidence: 99%